2000
DOI: 10.1177/107754630000600303
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Diagnostics Based on Pattern Recognition of Statistical Parameters

Abstract: In this paper, a new bearing defect diagnostic and classification method is proposed based on pattern recognition of statistical parameters. Such a pattern recognition problem can be described as transformation from the pattern space to the feature space and then to the classification space. Based on trend analysis of six commonly used statistical parameters, four parameters, namely, RMS, Kurtosis, Crest Factor, and Impulse Factor, are selected to form a pattern space. A 2-D feature space is formulated by a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Also, the FMECA method classifies the FMs using risk priority numbers (RPN) that are calculated with three failure mode parameters: occurrence (Occ), detection (Det) and severity (Sev). So, the FMECA [11] allows the definition of the appropriate detection method and measures to be used in the diagnostics as well as in the prognostics of the failure modes.…”
Section: Prognostics Processmentioning
confidence: 99%
“…Also, the FMECA method classifies the FMs using risk priority numbers (RPN) that are calculated with three failure mode parameters: occurrence (Occ), detection (Det) and severity (Sev). So, the FMECA [11] allows the definition of the appropriate detection method and measures to be used in the diagnostics as well as in the prognostics of the failure modes.…”
Section: Prognostics Processmentioning
confidence: 99%
“…previous research work has shown that each feature is only effective for certain defect at certain stage. For example, spikiness of the acoustic emission signals indicated by Kurtosis implies incipient defects, whereas the high energy level given by the value of RMS indicates severe defects (Xi F and Krishnappa, 2000). A good performance assessment method should take advantage of mutual information from multiple features for system degradation (hazard) assessment.…”
Section: Background Of Gearbox Prognosticsmentioning
confidence: 99%
“…This inherently implies a need to consider the statistical distribution of the residual series. In fact, when the distribution is studied in detail, it alone offers clues about the state of damage of the system [5,6,14,15]. For that reason, this section is dedicated to observations made with regards to characteristics of the distribution of the residuals and direct comparison to the normal distribution.…”
Section: Normality Assumptionmentioning
confidence: 99%